2020
DOI: 10.1016/j.immuni.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Therapeutic Antibody Cocktail Reveals Determinants for Cooperative and Broad Ebolavirus Neutralization

Abstract: Graphical AbstractHighlights d Human mAbs of two epitope specificities bind cooperatively to the ebolavirus GP d Cooperativity is mediated by a mAb that enhances binding to a vulnerable GP epitope d A two-mAb cocktail exhibits enhanced potency against heterologous ebolaviruses d Two 30 mg/kg doses of the cocktail fully protected nonhuman primates (NHPs) challenged with EBOV SUMMARY Structural principles underlying the composition of protective antiviral monoclonal antibody (mAb) cocktails are poorly defined. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 81 publications
3
112
0
Order By: Relevance
“…Such viruses provide a facile system to select for spike mutations that evade antibody neutralization ( Case et al, 2020 ; Dieterle et al, 2020 ; Weisblum et al, 2020 ). We chose five potently neutralizing antibodies (IC 50 values ranged from 15 to 150 ng/mL), and used a high-throughput quantitative real-time cell analysis assay ( Gilchuk et al, 2020a , 2020b ) to select viral mutants that could escape each individual antibody at a concentration of 5 μg/mL, performing between 16 and 56 individual replicates for each antibody ( Figure 6A and S6A , B , C ). For four of the five antibodies, this process selected viral variants that we confirmed resisted neutralization by 10 μg/mL of the antibody used for the selection ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such viruses provide a facile system to select for spike mutations that evade antibody neutralization ( Case et al, 2020 ; Dieterle et al, 2020 ; Weisblum et al, 2020 ). We chose five potently neutralizing antibodies (IC 50 values ranged from 15 to 150 ng/mL), and used a high-throughput quantitative real-time cell analysis assay ( Gilchuk et al, 2020a , 2020b ) to select viral mutants that could escape each individual antibody at a concentration of 5 μg/mL, performing between 16 and 56 individual replicates for each antibody ( Figure 6A and S6A , B , C ). For four of the five antibodies, this process selected viral variants that we confirmed resisted neutralization by 10 μg/mL of the antibody used for the selection ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…To screen for escape mutations selected in the presence of individual antibodies or antibody cocktails, we used a real-time cell analysis assay (RTCA) and xCELLigence RTCA MP Analyzer (ACEA Biosciences Inc.) with modification of previously described assays (Gilchuk et al, 2020a;Weisblum et al, 2020) . Fifty (50) μL of cell culture medium (DMEM supplemented with 2% FBS) was added to each well of a 96-well E-plate to obtain a background reading.…”
Section: Selection Of Escape Mutants Using the Spike-expressing Vsvmentioning
confidence: 99%
“…Similarly, escape mutants to RBS bnAbs can be even more readily isolated [157,158]. Notwithstanding, studies in Zika virus, Ebola virus, HBV, and SARS-CoV-2 have shown that use of a well-designed antibody cocktail can minimize the emergence of escape mutants [159][160][161][162]. Thus, a universal influenza vaccine may need to induce a polyclonal response that targets both the RBS and stem domain to prevent or mitigate against escape.…”
Section: Ha-based Therapeutic and Vaccine Designmentioning
confidence: 99%
“…As a result, large panels of NAbs were isolated from human 59 survivors, vaccinated humans, and immunized animals (12,(34)(35)(36)(37)(38)(39). Crystallography (40)(41)(42)(43) and 60 electron microscopy (EM) (44)(45)(46)(47) have revealed multiple sites of vulnerability on EBOV GP. A 61 recent study of 171 monoclonal antibodies (mAbs) defined eight classes of epitopes (48), six of which can be recognized by broadly neutralizing antibodies (bNAbs) (9).…”
Section: Introductionmentioning
confidence: 99%